The Role of Blood Spot Dehydroepiandrosterone Sulfate Levels in Adjunct to Hand Wrist Radiographs as Skeletal Maturity Indicator - Shashikalakumari Venkatagiriappa; Achala Raman; Anuj Sharma (Galenos Yayinevi, 2016)
Objective:The purpose of this study was to find out whether blood spot Dehydroepiandrosterone Sulfate (DHEAs) levels can be used as Skeletal Maturity Indicators (SMI) by correlating them to hand-wrist maturation stages.Methods:The cross sectional study population consisted of 107 subjects (62 females and 45 males) 5-25 years old. Hand-wrist radiographs were obtained, and the subjects were divided into 5 groups based on the hand-wrist skeletal maturity stages. A blood spot sample was collected and immunoassayed for DHEAs. Analysis of variance was used to compare the mean DHEAs levels corresponding to the hand-wrist maturation stages. Pearson's correlations were performed to determine the DHEAs trends relating to the various hand-wrist maturation stages.Results:DHEAs levels increased continuously from the prepubertal stage to the acceleration, high growth velocity/peak, deceleration, and postpubertal stages (r=0.17), but the total increase was not found to be statistically significant (p=0.08).Conclusion:The blood spot DHEAs level cannot be used as an SMI in individuals. Nevertheless, it can be used in conjunction with hand wrist radiographs to predict and validate the skeletal maturation. The role of DHEAs in the termination of growth and residual growth may be a subject for further research.